1977
DOI: 10.1128/aem.34.1.23-29.1977
|View full text |Cite
|
Sign up to set email alerts
|

Thermal destruction of Clostridium botulinum spores suspended in tomato juice in aluminum thermal death time tubes

Abstract: The heat destruction characteristics of Clostridium botulinum spores suspended in tomato juice and phosphate buffer were determined by the survivor curve method with aluminum thermal death time tubes. Two type A strains of C. botulinum and a type B strain were evaluated. Strains A16037 and B15580 were implicated in outbreaks of botulism involving home-canned tomato products. Strain A16037 had a higher heat resistance than either 62A or B15580. The mean thermal resistance (D-values) for A16037 in tomato juice (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 23 publications
1
23
0
1
Order By: Relevance
“…Sorensen phosphate buffer (0.067 M, pH 7.0) was prepared by mixing 610 mL of a stock solution of 0.067 M sodium phosphate dibasic anhydrous (Na,HPO,) with 390 mL of a stock solution of 0.067 M potassium phosphate monobasic anhydrous (KH,PO,) (Odlaug and Pflug 1977). The buffer was dispensed in 1 50-mL quantities and sterilized by autoclaving at 121C for 10 min.…”
Section: Sorensen Phosphate Buffer Preparationmentioning
confidence: 99%
“…Sorensen phosphate buffer (0.067 M, pH 7.0) was prepared by mixing 610 mL of a stock solution of 0.067 M sodium phosphate dibasic anhydrous (Na,HPO,) with 390 mL of a stock solution of 0.067 M potassium phosphate monobasic anhydrous (KH,PO,) (Odlaug and Pflug 1977). The buffer was dispensed in 1 50-mL quantities and sterilized by autoclaving at 121C for 10 min.…”
Section: Sorensen Phosphate Buffer Preparationmentioning
confidence: 99%
“…In the present study, POD was found to be the most heat stable enzyme in sapota with a Z-value of 17.6 ∘ C. The Z-value was observed to be higher than the reported Z-value (9-10.7 ∘ C) for C. botulinum spores in various matrices. 38 Therefore, considering D-and Z-values of the enzymes along with D-and Z-values of microorganisms during fruit processing can hold better promise for producing stable products with improved shelf life.…”
mentioning
confidence: 99%
“…THE TECHNIQUE of heating small samples of foods in glass and aluminum tubes or plastic bags to simulate the effect of heat on quality has been widely used (Farkas, 1962;Odlaug and Pflug, 1977;Erdtsieck and Beumer, 1976). Saguy et al (1978a) used a more sophisticated steam-heated thermal unit.…”
Section: Resultsmentioning
confidence: 99%